Two new species of scale mites (Acari: Pterygosomatidae) parasitizing Agama agama (Sauria: Agamidae) from Kenya - Fajfer, Monika (Zootaxa, 2013)
Two new species of pterygosomatid mites Pterygosoma garissi sp. nov. and P. fragilis sp. nov. (Acari: Pterygosomatidae) are described from the agamid lizard Agama agama (Sauria: Agamidae) from Kenya. P. garissi sp. nov. is similar to P. annectans Jack, 1962 but in the new species the peripheral setae are slightly expanded apically, 3 pairs of setae are situated on the coxal fields I and and 2 pairs on II coxal fields, all pseudoanal setae are paddle-shaped with minute spicules on the apical part, setae dFIV are absent and lTrIV present. P. fragilis sp. nov. is most closely related to P. garissi sp. nov. but differs by the presence of setae n on the subcapitulum, the hypostome with several denticles at the apex, the fixed cheliceral digit bearing a spinous process, the presence of 8–9 pairs of the peripheral setae, 1–2 pairs of genital setae g, and by the cheliceral shaft 2.1 times longer than the cheliceral base.